MENGKRITISI EKSEPSI TIDAK BERKUASANYA HAKIM DALAM PEMERIKSAAN PERKARA PERDATA DI PENGADILAN NEGERI - Marjo Marjo (Masalah-Masalah Hukum, 2010)
In procedural of civil law, it known several kind of exception one of then is exception about judge's lack authority (to try a case). The explanation of exception in investigation civil case in district court is the protest from defendant to plaintiff's allegation which is in direct concern about lawsuit, that is contain claim of cancelled convention. An then, the explanation of exception about judge's lack authority (to try a case) is exception that explain court does not able to chec the convention. Existence of exception about judge's lack authority (to try a case) in investigation civil case is existence of defendant's answer, there is the right for defendant is not a duty. The kind ofexeption about judge's lack authority (to try a case) in investigation in civil case in district court can divide ito 2, there is exception about judge's lack authority (to try a case) in relative competence and exception about judge's lack authority (to try a case) in absolute competence. Exception about judge's lack authority (to try a case) in ruled in Section 121 subsection (2), Section 125 subsection (2), Section 133, andSection 134HIR